PENGARUH PENERAPAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH KOTA PRABUMULIH - Khonsa Syadanna; Kiagus Zainal Arifin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2021)
The purpose of this study was to determine the effect of implementing a control environment on the quality of the Prabumulih City Government financial reports, the impact on the quality of the Prabumulih City Government financial reports, the control of the quality of the Prabumulih City Government financial reports, information and communication on the quality of the Prabumulih City Government financial reports, and the monitoring of report quality. Prabumulih City Government finances and determining the impact of control, control, control, and communication on the quality of Prabumulih City Government financial reports concurrently. This study's population consists of 28 OPD Prabumulih City's head of OPD, OPD treasurer, goods administration, and finance administration. Using a questionnaire sent to the heads of OPD, treasurer of OPD, goods administration, and financial administration in 28 OPD Prabumulih City, this study collects primary data. There were a total of 112 distributed questionnaires, of which 96 were returned. The strategy for selecting samples is saturated sample. This study used the approach of multiple linear regression analysis for its analysis. The findings of this study indicate that the control environment, impact, control activities, information and communication, and partial control have a positive and statistically significant effect on the quality of the financial statements of the Prabumulih City government, while the control environment, control activities, information and communication, and monitoring also have a positive impact. Prabumulih is essential to the quality of the government's financial statements.